Iterative Solutions for the Differential Equation with p-Laplacian on Infinite Interval - Guoying Zhao; Ying Wang (Journal of Function Spaces)
This paper systematically investigates a class of fourth-order differential equation with p-Laplacian on infinite interval in Banach space. By means of the monotone iterative technique, we establish not only the existence of positive solutions but also iterative schemes under the suitable conditions. At last, we give an example to demonstrate the application of the main result.